Power Imbalance and Employee Silence: The Role of Abusive Leadership, Power Distance Orientation, and Perceived Organisational Politics. Issue 3 (10th October 2018) - Lam, Long W.; Xu, Angela J.
Abstract : Employee silence is a costly but omnipresent phenomenon in modern organisations. In this study, we focus on two forms of silence: defensive silence based on fear and acquiescent silence based on resignation. Given the power imbalance in supervisor–subordinate relationships, we hypothesise that abusive supervision is an antecedent of subordinates' defensive silence and that a subordinate's power distance orientation affects acquiescent silence. We investigate the interaction effects of abusive supervision and power distance orientation on these two types of silence. Perceived organisational politics may also aggravate such interactive effects. Based on data collected from 159 junior employees in China in two periods, we find that abusive supervision is associated with employee defensive silence and moderates high‐power‐distance employees' tendency to engage in acquiescent silence. When perceiving high politics in the organisation, high‐power‐distance employees are more sensitive to abusive supervision and engage in more defensive silence. A highly political organisational context also accentuates abusive supervision's moderating effect on the relation between employees' power distance orientation and acquiescent silence. We conclude with theoretical and practical implications for the silence literature.